A.04 Functional investigations of CIC and ATXN1L in Oligodendroglioma. (2nd June 2017) - Wong, D; LeBlanc, V; Chittaranjan, S; Chan, S; Song, J; Lee, M; Marra, M; Yip, S
Abstract : Background: Oligodendroglioma (ODG), a molecularly defined subtype of glioma, is a treatment responsive, slow growing tumour strongly associated with IDH mutation and 1p19q co-deletion. Mutations in Capicua ( CIC ), located on chromosome 19q, have been found in up to 70% of IDH mutated, 1p19q co-deleted ODGs; suggesting that loss or altered function of CIC may be crucially associated with ODG's unique biology. CIC and ATXN1L have previously been implicated in neurodegeneration, however, this interaction has not been studied in cancer.Methods: Transcriptome profiling of CIC knockout HEK293 cell lines generated using CRISPR was performed using microarray. CIC and ATXN1L interaction was confirmed using immunoprecipitation and immunofluorescence. Transcript and protein changes of CIC targets were tested using RT-qPCR and Western blot following ATXN1L siRNA knockdown.Results: Transcriptomic profiling of CIC knockout cell lines resulted in a list of candidate CIC target genes validated against clinical samples. Immunoprecipitation and immunofluorescence confirmed CIC and ATXN1L interaction. Derepression of candidate CIC targets at transcript and protein levels was seen upon siRNA knockdown of ATXN1L.Conclusions: The interaction between CIC and ATXN1L is necessary for the repression of CIC target genes, including known oncogenes. Further research into the relationship between CIC and ATXN1L may lead potentially novel avenues of therapeutic approaches for less favorable gliomas.